2015
DOI: 10.1016/j.carbon.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

N-doped monolithic carbon aerogel electrodes with optimized features for the electrosorption of ions

Abstract: A B S T R A C T N-doped carbon aerogels were synthesized by the polycondensation of resorcinolformaldehyde-melamine mixtures. The prepolymerization of the precursors was determinant for the preparation of meso/macroporous aerogels with varied nitrogen content, regardless the solution pH and M/R molar ratio. The effect was more pronounced at pH 6, as the hydrogels prepared by the one-step route displayed essentially a microporous character, as opposed to the mesoporous network after prepolymerization. The prepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 55 publications
5
69
0
Order By: Relevance
“…This signal contribution was ascribed to electronic transitions of π-electrons in the aromatic ring system of uric acid which constitutes a heterocyclic and bicyclic purine derivative. Such shake-up spectral features are known for aromatic rings [56], and they have been reported for purine systems such as poly adenosine [57]. …”
Section: Resultsmentioning
confidence: 99%
“…This signal contribution was ascribed to electronic transitions of π-electrons in the aromatic ring system of uric acid which constitutes a heterocyclic and bicyclic purine derivative. Such shake-up spectral features are known for aromatic rings [56], and they have been reported for purine systems such as poly adenosine [57]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the degrees of graphitization were evaluated by the Raman spectra. As shown in Figure b, two peaks located at 1340 and 1585 cm −1 can clearly be observed, which can be indexed to D‐band (disordered carbon atoms) and G‐band (graphitic carbon atoms), respectively . The I D / I G ratios of GTCo800, GTCo900, and GTCo1000 are 0.99, 0.93, and 0.95, respectively, indicating that GTCo900 has the highest degree of graphitization.…”
Section: Methodsmentioning
confidence: 92%
“…As shown in Figure 1b, two peaks located at 1340 and 1585 cm À 1 can clearly be observed, which can be indexed to Dband (disordered carbon atoms) and G-band (graphitic carbon atoms), respectively. [45] The I D /I G ratios of GTCo800, GTCo900, and GTCo1000 are 0.99, 0.93, and 0.95, respectively, indicating that GTCo900 has the highest degree of graphitization. Furthermore, the peak at 670 cm À 1 can also be detected, which corresponds to Co 9 S 8 , which confirm that these catalysts consist of carbon and crystalline Co 9 S 8 .…”
mentioning
confidence: 99%
“…Porous carbon materials, such as mesoporous carbon, carbon aerogel, activated carbon, and graphene, have received considerable attention owing to their various advantageous properties, such as large surface area and tunable pore structure [1][2][3][4]. Among these materials, ordered mesoporous carbon (OMC) nanoparticles could provide ready access because of their shorter diffusion lengths and continuously interconnected pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…graphitic character and hence low electrical conductivity [7,8]. It has been shown that the electrical conductivity of carbon can be improved by nitrogen modification [1][2][3]. According to experimental investigations and quantum mechanical calculations, doping of nitrogen in carbon frameworks, especially in the form of pyridinic and graphitic quaternary nitrogen, can significantly improve the electrical conductivity [9].…”
Section: Introductionmentioning
confidence: 99%